2018
DOI: 10.1053/j.gastro.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids Reduce Risk of Death Within 28 Days for Patients With Severe Alcoholic Hepatitis, Compared With Pentoxifylline or Placebo—a Meta-analysis of Individual Data From Controlled Trials

Abstract: In a meta-analysis of 4 controlled trials, we found corticosteroid use to reduce risk of death within 28 days of treatment, but not in the following 6 months. This loss of efficacy over time indicates a need for new therapeutic strategies to improve medium-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
148
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 170 publications
(158 citation statements)
references
References 33 publications
1
148
0
9
Order By: Relevance
“…The decision to treat severe alcoholic hepatitis with corticosteroids has been a contentious issue for many years. There is some short‐term improvement in outcome with such treatment when given to patients with a DF greater than 32 . However this benefit does not extend beyond 28 days and it has not been possible to define which of these patients will respond before starting treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The decision to treat severe alcoholic hepatitis with corticosteroids has been a contentious issue for many years. There is some short‐term improvement in outcome with such treatment when given to patients with a DF greater than 32 . However this benefit does not extend beyond 28 days and it has not been possible to define which of these patients will respond before starting treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study was not powered to examine survival differences at this higher MDF threshold, and subsequent studies have not substantiated this observation. The meta‐analysis using individual patient data from 11 RCTs demonstrated that patients with AH in the highest MDF quartile (≥68) had statistically similar responses to corticosteroid treatment compared to those with lower MDF scores . This suggests that even very sick patients based on MDF, in the absence of contraindications, can benefit from corticosteroid treatment.…”
Section: Diagnosis and Treatment Of Alcohol‐associated Liver Diseasesmentioning
confidence: 98%
“…Mathurin et al combined the individual patient data sets of three, five, then recently 11 RCTs, which ultimately included 2,111 patients. In the latest iteration, corticosteroid treatment significantly reduced mortality at 28 days compared with placebo (hazard ratio, 0.64; 95% CI, 0.48‐0.86), representing a 36% risk reduction …”
Section: Diagnosis and Treatment Of Alcohol‐associated Liver Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mortality rates as high as 50% have been reported at 3 months without treatment . Currently, corticosteroid therapy is the only available option that provides a limited (albeit significant) reduction in short‐term mortality . The Lille score or the combination of the Lille and the model for end stage liver disease (MELD) scores have been proposed as tools for helping physicians to decide whether or not corticosteroids should be maintained after one week of treatment according to the probability of improvement in survival if corticosteroids are maintained .…”
Section: Introductionmentioning
confidence: 99%